Frozen dreams : based on a true story - Tatematsu, Wahei; Gabriel, Philip, 1953- (London : Peter Owen, 2012)
'Based on a real-life tragedy in 1965, this novel tells the story of a party of climbers on the Hidaka mountain range on Japan's northern island. In spite of weather warnings, six men attempt an ascent on the highest peak, Mount Poroshiri - a fateful decision that costs all their lives as they are caught up in an avalanche. Miraculously, one climber, Odagiri, is known to have survived for four days after his companions had frozen to death. The reader enters the mind of Odagiri trapped in snow, half-frozen, half-asleep, and revisiting his past as death slowly creeps upon him, telling his own story and that of an adventure gone wrong'--
Translated from the Japanese.
Keywords: Hidaka Mountain Range (Japan) -- Fiction